Indian Honey Exports in Context to Standards of the International Market - Shanmuganathan S; Gopalsamy S (Business, Management and Economics: Research Progress Vol. 7, 2024)
The honey bee has a significant number of antioxidants and flavonoids. These benefits have heightened honey’s appeal in the home remedy market, establishing it as a prominent product in the organic sector. The honey bee is one of humanity’s most significant insects. Bees and humans are two of the rare species that complement one another. By 2025, the organic honey market is expected to grow to a value of 923.6 million US dollars worldwide. China leads the world in honey production volume (31.4%), followed by Turkey (6.9%), Russia (5%), Iran (5%), and other nations (approximately 41% combined). The workflow involved in exporting Indian honey from farmers to manufacturers is covered in this study chapter, along with the legal specifications needed to export Indian honey to the global market. The last two years have seen a major slowdown in the growth of the Indian honey business due to a decrease in export orders. Measures implemented by the national bee board to reinvigorate the industry have been discussed. In addition to routine authenticity testing, the presence of natural chemicals like pinocembrin, apigenin, cardamomin, luteolin, quercetin, chrysin, and tectorigenin in honey can help determine its country of origin. NBB must accurately align export data with beekeeper colony production data.